The social policy of Lionel Jospin’s government in France (1997–2002) - Kolb, Eugene G. (Journal of the Belarusian State University. History, 2021)
The social policy of Lionel Jospin’s government was focused on solving the problems of unemployment and social inequality, which in the 1990s were perceived by the population as the main problems of the country. This corresponded with traditions and ideological principles of the French left and the methods used were very close to the policies of previous left governments. One of the distinguishing features of Jospin’s government was the close attention it gave to family issues and protection of the interests of disabled people. Another distinctive feature was active use of the strong-willed approach, from which left-wing governments had retreated since 1983 under the influence of economic realities. At the same time the government took into account the necessity of economic development and refused to strengthen state control over labor relations as well as avoiding any large-scale actions to increase employees income. Despite the government’s pragmatism, for the first time since left forces came to power its social policy did not cause obvious disappointment among the part of the population close to the left camp. Despite all the external success of social policy results, it did not deliver the expected electoral effect due to the contradictions contained in it.
Keywords: France; social policy; left political camp; French Socialist Party